Empathy and forgiveness on student victims of toxic relationships - Felani Omie Timpal; Arthur Huwae (International Journal of Public Health Science (IJPHS), 2026)
A toxic relationship shows a negative impact on the physical and mental condition of individuals who have undergone the subject. Even though the students have experienced unpleasant conditions in life, to continue her life journey, the student needs to make peace and build a concept of forgiveness for the circumstances that are formed through empathy. This research aims to determine the relationship between empathy and forgiveness in students who have been victims of toxic relationships. The method used is quantitative correlational. An equal number of 355 students who had been victims of toxic relationships came to be participants in this study, with the sampling technique used, specifically, incidental sampling. This study uses a scale, namely the Interpersonal Reactivity Index (α = 0.863) and Transgression-Related Interpersonal Motivations -18 (α = 0.843). The research data analysis method uses the product-moment correlation test from Karl Pearson. The results show that there was a significant positive relationship between empathy and forgiveness (r = 0.228 and sig = 0.000 (p<0.01). Empathy contributed 5.2% to forgiveness. It appears that empathy is one of the factors associated with increased forgiveness in students who have been victims of a toxic relationship.